The functionalization of gold nanoparticles as a novel platform for the highly efficient electrochemical detection of silver ions. Issue 2 (12th November 2020) - Xiao, Zhourui; Meng, Han; Qin, Xuefei; Sang, Xueqing; Zhang, Yun; Yuan, Yali
Abstract : A novel platform was constructed by the functionalization of gold nanoparticles for the highly efficient electrochemical detection of silver ions. Abstract : Herein, a novel electrochemical biosensor was constructed for the highly efficient detection of silver ions. A porous platform constructed with functionalized gold nanoparticles (AuPP) was electropolymerized on the gold electrode surface. The obtained polymer, analogous to a metal–organic framework, was used as the sensing platform together with cytosine–Ag + –cytosine interaction for dual signal amplification. The scanning electron microscopy (SEM) image of the AuPP platform exhibited a porous structure and considerable binding sites for C-riched single stranded DNA, leading to predictable silver ion preconcentration. Based on this strategy, the biosensor showed that the peak current in differential pulse voltammetry rose linearly as the concentration of silver ion increased from 0.005 to 3 μM with a detection limit of 1.3 nM. In addition, in the presence of other metal ions, such as Pb 2+, Mn 2+, Ni 2+, Co 2+, Cu 2+, Zn 2+, Na +, Ca 2+, and Cd 2+, at the same concentration, the current signal remained almost unchanged, manifesting high selectivity for Ag + . This proposed sensor might exhibit a novel fabrication method for metal ion detection with the aid of multiple AuPP materials by designing ligands with different functional groups.